#### Answer

$-13$

#### Work Step by Step

$6.5(-4.8)\div(-0.3)\div(-2)^3 = 6.5*(-4.8)\div(-0.3)\div(-8) = -13$

Published by
Pearson

ISBN 10:
0321825535

ISBN 13:
978-0-32182-553-7

$-13$

$6.5(-4.8)\div(-0.3)\div(-2)^3 = 6.5*(-4.8)\div(-0.3)\div(-8) = -13$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.